Phase Diagram of Binary Mixture E7:TM74A Liquid Crystals - Delica, Serafin; Estonactoc, Melvin; Micaller, Mary Claire; Cada, Leonorina; Domingo, Zenaida (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
Although there are many liquid crystalline materials, difficulty is often experienced in obtaining LCs that are stable and has a wide mesophase range. In this study, mixtures of two different LCs were used to formulate a technologically viable LC operating at room temperature. Nematic E7(BDH) and cholesteric TM74A were mixed at different weight ratios at 10% increments. Transition temperatures were determined via Differential Scanning Calorimetry and phase identification was done using Optical Polarizing Microscopy. The phase diagram showed the existence of three different phases for the temperature range of 10-80°C. Mixtures with 0-20% E7 exhibit only the cholesteric-nematic mesophase, which could be due to the mixture's being largely TM74A and its behavior in the temperature range considered is similar to the behavior of pure TM74A. With an increase in the concentration of E7, the smectic phase of the pure cholesteric was enhanced, as seen from the increased transition to the cholesteric-nematic phase and a broader smectic range. The cholesteric-nematic to isotropic transition increased as the nematic concentration increases, following the behavior expected from LC mixtures. For mixtures that are largely nematic (more than 50% E7), the smectic phase has vanished and the cholesteric-nematic phase dominated from 30-60°C.
Keywords: liquid crystals; phase diagrams